(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In the modern classroom, educators are constantly seeking engaging and meaningful ways to help students develop language skills. One increasingly popular approach is Project-Based Learning (PBL). Rather than focusing on isolated grammar exercises or textbook drills, PBL invites students to use language authentically, in the context of solving real problems, creating prducts, or completing tasks that matter. This article explores how implementing PBL can significantly enhance language learning by making it more relevant, student-centred, and skillintegrated.